Pedagogical Competence of Elementary School Teachers in Implementing Learning According to the Merdeka Curriculum - Amir, Mohammad Faizal; Indrawati, Tasya Juli; Hidayanti, Andina Nurnida; Anindhita, Putri Bulqhis; Safitri, Nur Fajriah (Procedia of Social Sciences and Humanities, 2024)
This research identifies and evaluates teachers' pedagogical competencies in implementing the Independent Learning Curriculum at SD Muhammadiyah. The Independent Curriculum allows teachers to design learning that suits students' characteristics and potential, encourages active student participation, and utilizes technology in the learning process. The research method used is descriptive qualitative with a case study approach involving semi-structured interviews, classroom observations, and document analysis. The research results show that most teachers understand the Independent Learning Curriculum and can implement it effectively. Teachers at SD Muhammadiyah demonstrate good pedagogical competence, especially in understanding student characteristics, designing learning, implementing the learning process, and conducting learning evaluations. Hopefully, these findings can positively contribute to improving the quality of education in Indonesia, especially in implementing the Independent Learning Curriculum.